Report concerning the colaborative study for establish of reference standard eficacity of Rifamycin - Simona Sturzu; Daniela Tîrsînoagă; Ioana Tihulcă; Mariana Dumitrache; Alina Drăghici; Valentina Năstase (Medicamentul Veterinar)
The Microbiology Laboratory from the Institute for the Control of Veterinary Biological Products and Medicines participated in a collaborative study in order to determine the potency of rifamycin CRS, batch 4, according to the protocol sent by the EDQM (European Directorate for the Quality of Medicines) - coordinating of the study. The purpose of the study was to establish the potency of the batch 4 rifamycin in the characterization of the substance as reference standard. Potency was determined by microbiological method, based on comparison of the inhibition zones of growth of micro-organisms sensitive to those of a reference standard, as specified in European Pharmacopoeia, Chapter 2.7.2. - Microbiological testing of antibiotics. After analysis of received data from participants and their statistical processing by the EDQM, the potency of the batch 4, rifamycin - reference materials, was established in 870 UI/mg.